Improved method for anti-corrosion pretreatment of metal surfaces comprising steel, galvanized steel, aluminum, aluminum alloys, magnesium and / or zinc-magnesium alloys
By using the improved method of using acidic aqueous composition A and aqueous composition B, the corrosion layering problem of metal surfaces such as galvanized steel is solved, and better corrosion protection and coating stability are achieved.
Patent Information
- Application Number
- CN202411796242.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-09-15
- Filing Date
- 2017-09-06
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively solve the corrosion layering problem of metal surfaces including steel, galvanized steel, aluminum, aluminum alloy, magnesium and/or zinc-magnesium alloys, especially on galvanized steel.
An improved method comprising acidic aqueous composition A and aqueous composition B, which comprises a compound of titanium, zirconium and hafnium, and composition B comprises a (meth)acrylate resin and a phenolic resin, contacting the metal surface by different contact sequences or simultaneously to improve the properties of the coating and corrosion protection effect.
It significantly improves the corrosion protection effect of metal surfaces such as galvanized steel, reduces corrosion and layering, and improves the adhesion and stability of the coating.
Smart Images

Figure BDA0005176784290000102 
Figure BDA0005176784290000111 
Figure BDA0005176784290000121
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 201780056502.8, application date September 6, 2017, and invention name "Improved method for anti-corrosion pretreatment of metal surfaces containing steel, galvanized steel, aluminum, aluminum alloy, magnesium and / or zinc-magnesium alloy".
[0002] The present invention relates to an improved method for the anti-corrosion pretreatment of metal surfaces comprising steel, galvanized steel, aluminum, aluminum alloys, magnesium and / or zinc-magnesium alloys. It further relates to a composition for improving the anti-corrosion pretreatment of the metal surface, a concentrate for preparing the composition, a correspondingly coated metal surface and a correspondingly coated metal substrate.
[0003] It is known to coat metal surfaces with aqueous compositions comprising compounds of titanium, zirconium and hafnium, organoalkoxysilanes, their hydrolysis and / or condensation products and other components.
[0004] The corrosion protection of the treated metal substrate is achieved by the resulting coating and the adhesion of other layers such as paint or varnish can also be improved to a certain extent.
[0005] The prior art also discloses the addition of specific acid-stable polymers to the above-mentioned compositions. In this way, the properties of the formed layer can be improved.
[0006] However, there remains the problem of corrosion delamination which has hitherto not been satisfactorily solved even with the use of said polymers, in particular in the case of surfaces comprising steel, galvanized steel, aluminum, aluminum alloys, magnesium and / or zinc-magnesium alloys.
[0007] The object of the present invention is therefore to overcome the disadvantages of the prior art and to provide an improved method for the corrosion pretreatment of metal surfaces comprising steel, galvanized steel, aluminum, aluminum alloys, magnesium and / or zinc-magnesium alloys, in particular to produce corrosion protection on galvanized steel.
[0008] This object is achieved by the method according to claim 1 , the aqueous composition according to claim 21 , the concentrate according to claim 22 , the metal surface according to claim 23 and the use of the metal substrate according to claim 24 .
[0009] In the method of the present invention for the anti-corrosion pretreatment of a metal surface comprising steel, galvanized steel, aluminum, aluminum alloy, magnesium and / or zinc-magnesium alloy, the metal surface is contacted with:
[0010] i) an acidic aqueous composition A comprising a1) at least one compound selected from the group consisting of titanium, zirconium and hafnium compounds, and
[0011] ii) an aqueous composition B comprising b1) at least one (meth)acrylate resin and b2) at least one phenolic resin,
[0012] The metal surface
[0013] i) first contacting with composition A and then contacting with composition B,
[0014] ii) first contacting with composition B and then contacting with composition A, and / or
[0015] iii) contacting with composition A and composition B simultaneously.
[0016] definition:
[0017] For the purposes of the present invention, "aqueous compositions" include compositions which comprise not only water as solvent / dispersion medium but also less than 50% by weight, based on the total amount of solvents / dispersion medium, of other organic solvents / dispersion media.
[0018] For the purposes of the present invention, "calculated as hexafluorozirconic acid" refers to the hypothetical case in which all molecules of component a1) in composition A are hexafluorozirconic acid molecules, ie H2ZrF6.
[0019] "Complex fluoride" encompasses not only the deprotonated form but also the corresponding mono- or polyprotonated forms.
[0020] For the purposes of the present invention, "(meth)acrylate resins" in component b1) are copolymers which comprise at least one acrylate and / or methacrylate as monomer units.
[0021] The wording "make the metal surface
[0022] i) first contacting with composition A and then contacting with composition B,
[0023] ii) first contacting with composition B and then contacting with composition A, and / or
[0024] iii) contacting with composition A and composition B simultaneously" should be interpreted as meaning that the following embodiments are also covered:
[0025] The metal surface is contacted sequentially with a first composition B (pre-rinse), composition A and a second composition B (post-rinse), wherein the first and second compositions B may also be chemically identical.
[0026] Before, after and / or between the contact with composition A and composition B, the metal surface is contacted with one or more other compositions, in particular a rinsing composition, and / or completely or partially dried.
[0027] The expression "the metal surface […] is brought into contact simultaneously with composition A and composition B" should be interpreted as meaning that it can also be brought into contact with a single composition, that is, an aqueous composition comprising all components a1), b1) and b2), and optionally further components of compositions A and B (see below).
[0028] i) Composition B:
[0029] According to a preferred embodiment, the metal surface is first contacted with composition A and then with composition B, which means that composition B is used as post-rinse liquid.
[0030] According to the invention, by adding the at least one (meth)acrylate resin b1) and the at least one phenolic resin b2) to composition B, the properties of the resulting coating, in particular the corrosion protection of galvanized steel, can be significantly improved.
[0031] Here, in composition B, the (meth)acrylate resin b1) comprises not only at least one acrylate and / or methacrylate but also monomer units selected from (meth)acrylic acid, vinylphosphonic acid and vinylsulfonic acid, preferably (meth)acrylic acid.
[0032] "(Meth)acrylic acid" refers to acrylic acid and / or methacrylic acid, and the corresponding deprotonated forms.
[0033] Particularly preferably, the (meth)acrylate resin b1) is a copolymer of methacrylate and acrylic acid, particularly preferably a copolymer of methyl methacrylate and acrylic acid, the copolymer preferably comprising 80-98% by weight of methyl methacrylate and 2-20% of acrylic acid (total: 100% by weight), more preferably 85-95% by weight of methyl methacrylate and 5-15% by weight of acrylic acid (total: 100% by weight).
[0034] The at least one (meth)acrylate resin b1) is preferably a random copolymer.
[0035] Furthermore, the at least one (meth)acrylate resin b1) preferably additionally contains hydroxyl, silyl, alkyl, aryl, heteroalkyl, heteroaryl, thio, amino, amide, nitrile, epoxy, mercapto, urea, nitro, halogen and / or cyano groups, more preferably hydroxyl, silyl, alkyl, amino and / or epoxy groups.
[0036] Particularly preferably, the at least one (meth)acrylate resin b1) additionally contains hydroxyl groups and / or silyl groups. These additional groups are preferably located on the alcohol residues of the (meth)acrylate monomer units and have the advantage of being able to form covalent bonds with metal surfaces and / or other coating (more particularly paint and varnish) components.
[0037] The mass average molecular weight of the at least one (meth)acrylate resin b1) is preferably 1000-500000 g / mol, more preferably 3000-250 000 g / mol, particularly preferably 5000-20 000 g / mol, more preferably 8000-17 000 g / mol, particularly preferably 10 000-15 000 g / mol.
[0038] The at least one phenolic resin b2) in composition B is preferably prepared by acidic condensation of formaldehyde and phenol, and preferably the molar ratio of formaldehyde to phenol is less than 1:1 (novolac), and / or is preferably prepared by alkaline condensation of formaldehyde and phenol and preferably contains reactive methylol groups, the benzene rings of which are linked to one another via methylene groups and also via ether bridges (resole phenolic resins).
[0039] Particularly preferably, the at least one phenolic resin b2) is a resole phenolic resin.
[0040] The mass average molecular weight of the at least one phenolic resin b2) is preferably 100-5000 g / mol, more preferably 130-3000 g / mol, more preferably 145-1000 g / mol, particularly preferably 160-600 g / mol, and especially preferably 190-300 g / mol.
[0041] According to a particularly preferred embodiment, composition B comprises as b1) a copolymer of methyl methacrylate and acrylic acid having 85-95% by weight of methyl methacrylate and 5-15% by weight of acrylic acid (total: 100%), with a mass average molecular weight of 8000-17 000 g / mol; and further comprises as b2) a resol phenolic resin having a mass average molecular weight of 145-1000 g / mol.
[0042] Composition B preferably comprises components b1) and b2) in a weight ratio of 1:1 to 10:1, more preferably 2:1 to 6:1, particularly preferably 3.1:1 to 4.6:1.
[0043] The total concentration of b1) and b2) in composition B is preferably 20-400 mg / l, particularly preferably 50-200 mg / l (calculated as solid addition).
[0044] The pH of composition B is preferably 3-9, particularly preferably 3-6, and especially preferably 4-5. A pH of 4-5 is advantageous, especially if composition B comprises a conversion bath.
[0045] Surprisingly, it has been found that certain ionic substances contained in composition B may under certain circumstances destabilize the at least one (meth)acrylate resin b1) and the at least one phenolic resin b2) in composition B and may lead to aggregation and precipitation of these components.
[0046] Composition B may advantageously comprise a stabilizer b3). Surprisingly, this stabilizer reduces the sensitivity of composition B to certain ionic species and also enables composition B to operate within a wider pH range.
[0047] Such stabilizers are advantageous in particular if the metal surface is contacted with a single aqueous composition comprising all components a1), b1) and b2), i.e. if the resin mixture b1) + b2) according to the invention is added to the conversion bath. Otherwise, in the acidic environment of the conversion bath (e.g. pH 4.8), the resin mixture tends to aggregate, causing the bath to become unusable over time.
[0048] The stabilizer b3) preferably comprises at least one triblock copolymer of the formula I:
[0049] PEOx-PPOy-PEOz(I)
[0050] PEO is polyethylene oxide, PPO is polypropylene oxide, x and z are in each case integers from 4 to 12, and y is an integer from 35 to 65.
[0051] Preferably, x and z are in each case an integer from 6 to 10, and y is an integer from 40 to 60. More preferably, x and z are in each case an integer from 7 to 9, and y is an integer from 45 to 55.
[0052] According to a particularly preferred embodiment, using PE 9200 (BASF, Germany) is used as stabilizer b3). It contains PEO8-PPO 50 -PEO8.
[0053] The mass concentration of the stabilizer b3) in the composition B (calculated as solid addition amount) is preferably 1.5-2.5 times, more preferably 1.8-2.2 times, the total concentration of the (meth)acrylate resin b1) and the phenolic resin b2).
[0054] According to a preferred embodiment, composition B further comprises at least one compound b4) of formula II:
[0055] R 1 O-(CH2) x -Z-(CH2) y -OR 2 (II)
[0056] Where R 1 and R 2 in each case independently of one another is H or a HO-(CH2) group w -, wherein w≥2, x and y are in each case independently of one another 1 to 4, and Z is a sulfur atom or a CC triple bond.
[0057] In this case, the at least one compound b4) of the formula II acts as a physical corrosion inhibitor which adsorbs on the metal surface via dipole-dipole interactions and van der Waals forces and thus prevents corrosive attack on the metal surface.
[0058] The at least one compound b4) is preferably present in a concentration of 10 to 300 mg / l, particularly preferably 50 to 180 mg / l (calculated as but-2-yne-1,4-diol).
[0059] The addition of this corrosion inhibitor has proven to be advantageous, in particular when composition B is used as a pre-rinse liquid.
[0060] According to a particularly preferred embodiment, composition B comprises not only components b1) and b2), but also components b3) and b4).
[0061] Composition B preferably comprises at least one molybdenum compound, more preferably heptamolybdate, as additional component b5), which in no way adversely affects the stability of composition B. In this case, the concentration of the at least one molybdenum compound is preferably 10 to 100 mg / l (calculated as molybdenum).
[0062] The addition of this molybdenum compound has proven to be advantageous, in particular when composition B is used as a post-rinsing liquid.
[0063] According to a first particularly preferred embodiment, composition B comprises not only components b1) and b2), but also components b3) and b5).
[0064] According to a second particularly preferred embodiment, composition B comprises not only components b1) and b2), but also components b4) and b5).
[0065] According to a particularly preferred embodiment, composition B comprises not only components b1) and b2), but also components b3), b4) and b5).
[0066] ii) Composition A:
[0067] The composition A preferably comprises, as component a1), at least one complex fluoride selected from the group consisting of complex fluorides of titanium, zirconium and hafnium.
[0068] Here, zirconium complex fluorides are further preferred. Here, zirconium can also be added as zirconyl nitrate, zirconyl carbonate, zirconyl acetate or zirconium nitrate, preferably as zirconyl nitrate. This applies analogously to the case of titanium and hafnium.
[0069] The content of the at least one complex fluoride is preferably 0.05-4 g / l, more preferably 0.1-1.5 g / l, particularly preferably about 0.25 g / l (calculated as hexafluorozirconic acid).
[0070] In a preferred embodiment, composition A comprises as component a1) at least two different complex fluorides, in particular complex fluorides of two different metal cations, particularly preferably complex fluorides of titanium and zirconium.
[0071] In composition A, the concentration of a1) is preferably 0.05-4 g / l, more preferably 0.1-1.5 g / l, more preferably 0.15-0.57 g / l, particularly preferably 0.20-0.40 g / l, very particularly preferably about 0.25 g / l (calculated as hexafluorozirconic acid).
[0072] The content of component a1) and optionally components a2) and a3) (see below) can be monitored by ICP-OES (optical emission spectroscopy with inductively coupled plasma) or photometric approximation during the metal treatment, so that (if necessary) further amounts of individual components or components can be introduced.
[0073] The composition A preferably additionally comprises a2) at least one compound selected from the group consisting of organoalkoxysilanes, organosilanols, polyorganosilanols, organosiloxanes and polyorganosiloxanes.
[0074] With respect to the at least one compound of component a2) in composition A, the prefix "organic" means at least one organic group which is directly bonded to a silicon atom via a carbon atom and cannot therefore be cleaved hydrolytically from the latter.
[0075] For the purposes of the present invention, "polyorganosiloxanes" are compounds which can be condensed from at least two organosilanols without forming polydimethylsiloxanes.
[0076] Composition A preferably comprises as component a2) at least one organoalkoxysilane, organosilanol, polyorganosilanol, organosiloxane and / or polyorganosiloxane, which in each case has at least one amino group, urea group, imide group, imino group and / or urea group per organoalkoxysilane / organosilanol unit. Further preferably, component a1) is at least one organoalkoxysilane, organosilanol, polyorganosilanol, organosiloxane and / or polyorganosiloxane, which in each case has at least one, in particular one or two, amino groups per organoalkoxysilane / organosilanol unit.
[0077] Particularly preferred are 2-aminoethyl-3-aminopropyltrimethoxysilane, 2-aminoethyl-3-aminopropyltriethoxysilane, bis(trimethoxysilylpropyl)amine or bis(triethoxysilylpropyl)amine or a combination of these as organoalkoxysilane / organosilanol units. Very particularly preferred are 2-aminoethyl-3-aminopropyltrimethoxysilane or bis(trimethoxysilylpropyl)amine or a combination of the two as organoalkoxysilane / organosilanol units.
[0078] In the composition A, the concentration of a2) is preferably 1 to 200 mg / l, more preferably 5 to 100 mg / l, particularly preferably 20 to 50 mg / l, very particularly preferably 25 to 45 mg / l (calculated as silicon).
[0079] Advantageously, composition A additionally comprises component a3) which is at least one cation selected from metal cations of transition groups 1-3 and 5-8 (including lanthanides) and main group 2 of the Periodic Table of the Elements as well as lithium, bismuth and tin, and / or at least one corresponding compound.
[0080] Component a3) is preferably at least one cation selected from the group consisting of cations of cerium and other lanthanides, chromium, iron, calcium, cobalt, copper, magnesium, manganese, molybdenum, nickel, niobium, tantalum, yttrium, vanadium, lithium, bismuth, zinc and tin, and / or at least one corresponding compound.
[0081] The composition A more preferably comprises zinc cations, copper cations and / or cerium cations and / or at least one molybdenum compound as component a3).
[0082] Composition A particularly preferably comprises zinc cations, very particularly preferably zinc cations and copper cations, as component a3).
[0083] The concentrations in composition A are preferably as follows:
[0084] - Zinc cation: 0.1-5 g / l
[0085] -Copper cation: 5-50g / l
[0086] -Cerium cation: 5-50 mg / l
[0087] - Molybdenum compounds: 10-100 mg / l (calculated as molybdenum).
[0088] According to a particularly preferred embodiment, composition A comprises not only component a1), but also components a2) and a3).
[0089] Depending on the specific requirements and circumstances, the composition A optionally comprises an additional component a4). This is at least one compound selected from substances influencing the pH, organic solvents, water-soluble fluorine compounds and colloids.
[0090] Here, the composition A preferably has a content of component a4) of 0.1 to 20 g / l.
[0091] The substance influencing the pH is preferably selected from nitric acid, sulfuric acid, acetic acid, methanesulfonic acid, hydrofluoric acid, ammonium / ammonia, sodium carbonate and sodium hydroxide. Here, it is further preferred to set the pH with nitric acid, ammonium carbonate and / or sodium carbonate.
[0092] The pH of composition A is preferably 0.5-5.5, more preferably 2-5.5, particularly preferably 3.5-5.3, very particularly preferably 4.0-5.0.
[0093] The organic solvent is preferably selected from methanol and ethanol. In practice, methanol and / or ethanol are present as reaction products of the hydrolysis of the organoalkoxysilane in the treatment bath.
[0094] The water-soluble fluorine compound is preferably selected from fluorine-containing compounds and fluoride anions.
[0095] The content of free fluoride ions in composition A is preferably 0.015-0.15 g / l, more preferably 0.025-0.1 g / l, particularly preferably 0.03-0.05 g / l.
[0096] The colloid is preferably metal oxide particles, more preferably metal oxide particles selected from the group consisting of ZnO, SiO2, CeO2, ZrO2 and TiO2.
[0097] Composition A preferably additionally comprises at least one cation selected from the group consisting of alkali metal ions, ammonium ions and corresponding compounds. It particularly preferably comprises sodium ions and / or ammonium ions.
[0098] Composition A may also contain phosphorus- and oxygen-containing compounds, such as phosphates and / or phosphonates. In addition, it may contain nitrates.
[0099] However, the content of sulfur-containing compounds, in particular sulfates, should preferably be kept as low as possible. The content of sulfur-containing compounds is particularly preferably below 100 mg / l (calculated as sulfur).
[0100] The metal surface to be treated (which has optionally been previously cleaned and / or pickled) can in each case be sprayed, dipped or immersed (gefluted) with composition A and / or composition B. The corresponding compositions can also be applied manually to the metal surface to be treated by wiping or brushing or by means of drums or rollers (coil coating process). Furthermore, the corresponding compositions can be deposited electrolytically on the metal surface to be treated.
[0101] The treatment time of the treated part is preferably 15 seconds to 20 minutes, more preferably 30 seconds to 10 minutes, and particularly preferably 45 seconds to 5 minutes. The treatment temperature is preferably 5-50°C, more preferably 15-40°C, and particularly preferably 25-30°C.
[0102] The method of the invention is also suitable for the coating of strips (coils). In this case, the treatment time is preferably from a few seconds to a few minutes, for example 1 to 1000 seconds.
[0103] The method of the present invention is capable of coating mixtures of various metallic materials in the same bath (referred to as multi-metal capability).
[0104] The metal surface to be treated preferably comprises steel, galvanized steel, magnesium and / or a zinc-magnesium alloy; more preferably comprises steel and / or galvanized steel; particularly preferably comprises galvanized steel.
[0105] In particular, in the case of metal surfaces comprising galvanized steel, greatly improved corrosion protection after cathodic electrophoretic coating (CEC) was observed after coating by the method of the invention.
[0106] This is manifested, for example, in that only polyacrylates are used in composition B instead of a combination of at least one (meth)acrylate resin b1) and at least one phenolic resin, compared with treatment by a process other than the process according to the invention.
[0107] The present invention also provides an aqueous composition B as described above for improving the anti-corrosion pretreatment of metal surfaces comprising steel, galvanized steel, aluminum, aluminum alloys, magnesium and / or zinc-magnesium alloys.
[0108] The invention furthermore provides a concentrate from which a composition B according to the invention can be prepared by dilution with water and optionally setting the pH.
[0109] Treatment baths comprising compositions B according to the invention are obtainable by diluting the concentrate with water and / or an aqueous solution, preferably by a dilution of 1:50,000 to 1:10, more preferably 1:10,000 to 1:10, particularly preferably 1:8,000 to 1:10, very particularly preferably about 1:5,000.
[0110] The present invention further provides a metal surface which comprises steel, galvanized steel, magnesium and / or a zinc-magnesium alloy and which is coated by the method according to the invention, wherein the coating formed has a layer weight determined by XRF (X-ray fluorescence analysis):
[0111] i) 5-500 mg / m 2 , preferably 10-200 mg / m 2 , particularly preferably 30-120 mg / m 2 , based only on component a1) (calculated as zirconium), and optionally ii) 0.5 to 50 mg / m2 , preferably 1-30 mg / m 2 , particularly preferably 2-10 mg / m 2 , based solely on component a2) (calculated as silicon).
[0112] The coating produced by the process of the present invention is used as a corrosion protection layer and also as a binder for other coatings.
[0113] Therefore, they can easily be further coated with at least one primer, paint, varnish, adhesive and / or paint-like organic composition. Here, at least one of these further coatings can preferably be cured by heating and / or radiation.
[0114] The coating produced by the process of the invention is preferably rinsed in order to remove excess polymer and interfering ions from the metal surface prior to further processing.The first further coating may be applied by a wet-on-wet process.
[0115] As paints / varnishes, preference is given to using cathodic electrophoretic coatings (CEC) based on epoxides and / or (meth)acrylates.
[0116] Finally, the present invention also provides the use of metal substrates coated by the process according to the invention in the automotive industry, rail vehicles, aerospace industry, plant construction, mechanical engineering, the building industry, the furniture industry, for the production of crash barriers, lamps, profiles, cladding or small parts, for the production of bodywork or body parts, individual components, pre-assembled or connected elements, preferably in the automotive or aerospace industry, for the production of devices or apparatuses, in particular household appliances, control devices, test devices or building elements.
[0117] The coated metal substrates are preferably used for the production of vehicle bodies or vehicle body parts, individual components and pre-assembly or connection elements in the automotive industry.
[0118] The present invention is illustrated by the following examples, which should not be construed as limiting. Example
[0119] i) Substrate and pretreatment:
[0120] Substrate:
[0121] Plates (10.5 x 19 cm) made of hot-dip galvanized steel (HDG) and other plates made of cold rolled steel (CRS) were used as substrates.
[0122] clean:
[0123] In all examples, the S 5176 (from Chemetall; contains phosphates, borates and surfactants) was used as a mild alkaline immersion cleaner. For this purpose, 15 g / l was prepared in a 50 L bath, heated to 60°C, and the substrate was cleaned by spraying at a pH of 10.0-11.0 for 3 minutes. The substrate was subsequently rinsed with tap water and deionized water.
[0124] Pre-rinsing (according to the invention):
[0125] Deionized water was used for pre-rinsing, wherein different amounts of a resin mixture were optionally added according to the present invention (see Table 1: "Resin mixture"). The resin mixture contained the following resol phenolic resin (exemplary structural formula) with a weight average molecular weight of 160 g / mol in a weight ratio of 1:3.7:
[0126]
[0127] and a (meth)acrylate resin having a mass average molecular weight of 9630 g / mol (determined by GPC), which is polymerized from 90 mol % of methyl methacrylate and 10 mol % of acrylic acid.
[0128] Optionally, a mixture of corrosion inhibitors (see Table 1: "Corrosion Inhibitors") is also added to the pre-rinsing liquid of the invention, so that the pre-rinsing liquid contains 62.5 mg / l of but-2-yne-1,4-diol and 50 mg / l of 1,4-bis(2-hydroxyethoxy)-2-butyne, resulting in a total of 112.5 mg / l of corrosion inhibitors.
[0129] Table 1
[0130]
[0131] *Solid content
[0132] The substrate was pre-rinsed at 20°C for 120 seconds with moderate agitation.
[0133] Conversion bath (according to the invention):
[0134] For the conversion bath, Additive 9936 (obtained from Chemetall, Germany; containing fluoride and zirconium compound) and optionally 9810 / 3 (obtained from Chemetall, Germany; contains aminosilanes, see Table 3: "Silanes") is added to a 50 L batch in an amount such that a zirconium concentration of 100-130 mg / l and a silane concentration (calculated as Si) of 20-30 mg / l are obtained. The bath temperature is set to 30° C. The pH and free fluoride content are set to pH=4.8 and 30-40 mg / l, respectively, by adding dilute sodium bicarbonate solution and dilute hydrofluoric acid (5% strength).
[0135] The pH was continuously corrected by adding dilute nitric acid.
[0136] Optionally, different amounts of the resin mixture already described for the pre-rinse solution according to the invention are added to the bath according to the invention (see Table 3: "Resin mixture").
[0137] Furthermore, different amounts of a specific triblock copolymer PEO8-PPO were added to the conversion bath of the present invention. 50 -PEO8( PE 9200; obtained from BASF, Germany, see Table 3: “Stabilizer”).
[0138] The bath (according to the invention) always also contains 400 mg / l of zinc. Optionally, 8-10 mg / l of copper in the form of copper nitrate is added to the bath (according to the invention).
[0139] Before passing the substrate through, the finished bath is aged for at least 12 hours to ensure that the chemical equilibrium in the bath is established. The conversion treatment is carried out for 120 seconds with moderate stirring. It is then rinsed with tap water and deionized water.
[0140] Post-rinsing of the present invention:
[0141] For the post-rinsing, deionized water was used, to which, according to the invention, different amounts of the resin mixtures already described for the pre-rinsing solution according to the invention (see Table 2: "Resin mixtures") and optionally 100 mg / l of the specific triblock copolymers already described for the conversion bath according to the invention (see Table 2: "Stabilizers") were added.
[0142] Optionally, 20 mg / l or 50 mg / l of molybdenum in the form of ammonium heptamolybdate was also added to the post-rinse liquid.
[0143] Table 2
[0144]
[0145] *Solid content
[0146] The substrate was post-rinsed for 90 seconds at 20°C with moderate agitation.
[0147] Various combinations of pre-rinsing liquid, conversion bath and post-rinsing liquid resulted in the examples and comparative examples shown in Table 3 below:
[0148] Table 3
[0149]
[0150]
[0151] *Calculated as Si; **Solid content
[0152] ii) Analysis, coating, bond strength and corrosion protection:
[0153] X-ray fluorescence analysis:
[0154] The layer weight (LW, mg / m2) on the pretreated substrate was determined by X-ray fluorescence analysis (XRF). 2 ). Here, the amount of zirconium applied was measured.
[0155] Surface coating:
[0156] The pretreated substrate was coated by CEC. To this end, the 800 (from BASF, Germany). A cumulative coating was subsequently applied. This was Daimler Black. The thickness of the coating was determined by means of a layer thickness measuring instrument in accordance with DIN EN ISO 2808 (2007 edition). It was 90-110 μm.
[0157] Corrosion testing:
[0158] In addition, four different corrosion tests were performed:
[0159] 1.) 60 corrosion cycles according to Volkswagen specification PV 1210 (2010-02 edition), 2.) according to VDA test sheet 621-415 and according to DIN EN ISO 20567-1 (1982 edition; method C)
[0160] Carry out 10 rounds of corrosion cycle test,
[0161] 3.) Corrosion cycle test Meko S test c according to DIN EN ISO 4628 8 (edition 2013-03), and 4.) Cathodic polarization according to FFM_C-AN_01941 (edition 2.0).
[0162] Layering:
[0163] In each case, the corrosion delamination in mm was determined in accordance with DIN EN ISO 4628-8 (2012 edition) (see Table 4: “Cd”). The reported values are in each case the average of three panels.
[0164] The results of the corrosion tests performed are summarized in Table 4 below:
[0165] Table 4
[0166]
[0167] nd = not determined
[0168] iii) Results and Discussion:
[0169] Table 4 shows that by adding the resin mixture of the invention to the pre-rinse, conversion bath and post-rinse, a reduction in corrosion delamination can be determined (see values of the examples and values of comparative examples CE1, CE8 and CE27).
[0170] By adding silane, there is again an improvement (see E18 and E17). Adding copper leads to an increase in the layer weight (see E15 and E16).
[0171] Despite the addition of the specific triblock copolymer, a clear increase in the service life of the conversion baths containing the resin mixtures of the invention occurred (results not shown). Aggregation of the resins in an acidic environment was largely prevented (E3-E7 vs. E2; E9 and E10).
[0172] Adding a corrosion inhibitor to the pre-rinse solution of the invention also resulted in further improvements (see E22 and E20), as did adding molybdenum to the post-rinse solution of the invention (see E29, E30 and E29).
Claims
1. A method for the anti-corrosion pretreatment of a metal surface comprising steel, galvanized steel, aluminum, an aluminum alloy, magnesium and / or a zinc-magnesium alloy, wherein the metal surface is contacted with: i) an acidic aqueous composition A comprising a1) at least one compound selected from the group consisting of titanium, zirconium and hafnium compounds, and ii) an aqueous composition B comprising b1) at least one (meth)acrylate resin and b2) at least one phenolic resin, The metal surface i) first contacting with composition A and then contacting with composition B, ii) first contacting with composition B and then contacting with composition A, and / or iii) contacting with composition A and composition B simultaneously.
2. A method according to claim 1, wherein the metal surface is first contacted with composition A and then with composition B.
3. The process according to claim 1 or 2, wherein the at least one (meth)acrylate resin b1) is a copolymer of methacrylate and acrylic acid. 4 . The process according to claim 3 , wherein the at least one (meth)acrylate resin b1) is a copolymer of methyl methacrylate and acrylic acid.
5. The process according to claim 4, wherein the at least one (meth)acrylate resin b1) comprises 80 to 98 wt. % of methyl methacrylate and 2 to 20 wt. % of acrylic acid (total: 100 wt. %), preferably 85 to 95 wt. % of methyl methacrylate and 5 to 15 wt. % of acrylic acid (total: 100 wt. %).
6. The process according to claim 1 , wherein the at least one (meth)acrylate resin b1) additionally comprises hydroxyl, silyl, alkyl, aryl, heteroalkyl, heteroaryl, thio, amino, amide, nitrile, epoxy, mercapto, urea, nitro, halogen and / or cyano groups, preferably hydroxyl, silyl, alkyl, amino and / or epoxy groups.
7. The process according to any of the preceding claims, wherein the at least one (meth)acrylate resin b1) has a mass average molecular weight of 1000 to 500 000 g / mol, preferably 3000 to 250 000 g / mol.
8. The process according to any of the preceding claims, wherein the at least one phenolic resin b2) is a resole phenolic resin.
9. The process according to any of the preceding claims, wherein the at least one phenolic resin b2) has a mass average molecular weight of 100 to 5000 g / mol, preferably 130 to 3000 g / mol.
10. The method according to any of the preceding claims, wherein composition B comprises components b1) and b2) in a weight ratio of 1:1 to 10:1, preferably 2:1 to 6:1, particularly preferably in a weight ratio of 3.1:1 to 4.6:
1.
11. The method according to any of the preceding claims, wherein the total concentration of b1) and b2) in composition B is 20-400 mg / l, preferably 50-200 mg / l (calculated as solid addition).
12. The process according to claim 1 , wherein composition B comprises as stabilizer b3) at least one triblock copolymer of formula I: PEOx-PPOy-PEOz(I) wherein x and z are in each case an integer from 4 to 12 and y is an integer from 35 to 65.
13. The method according to claim 12, wherein the mass concentration of the stabilizer b3) in the composition B (calculated as solid addition) is 1.5-2.5 times, preferably 1.8-2.2 times, the total concentration of the (meth)acrylic resin b1) and the phenolic resin b2).
14. The method according to any one of the preceding claims, wherein composition B additionally comprises at least one compound b4) of the formula II: R 1 O-(CH2) x -Z-(CH2) y -OR 2 (II) Where R 1 and R 2 in each case independently of one another is H or HO(CH2) w , wherein w≥2, x and y are in each case independently of one another 1 to 4, and Z is a sulfur atom or a CC triple bond.
15. The method according to claim 1, wherein composition B comprises at least one molybdenum compound as additional component b5).
16. The process according to any of the preceding claims, wherein component a1) in composition A is at least one complex fluoride selected from the group consisting of complex fluorides of titanium, zirconium and hafnium.
17. The method according to any of the preceding claims, wherein composition A additionally comprises a2) at least one compound selected from the group consisting of organoalkoxysilanes, organosilanols, polyorganosilanols, organosiloxanes and polyorganosiloxanes.
18. The process according to claim 17, wherein component a2) is at least one organoalkoxysilane, organosilanol, polyorganosilanol, organosiloxane and / or polyorganosiloxane which has in each case at least one amino, urea, imide, imino and / or urea group per organoalkoxysilane / organosilanol unit.
19. The method according to claim 1 , wherein composition A additionally comprises as component a3) 0.1 to 5 g / l of zinc cations, 5 to 50 mg / l of copper cations and / or 5 to 50 mg / l of cerium cations and / or 10 to 100 mg / l of at least one molybdenum compound (calculated as molybdenum).
20. A method according to any preceding claim, wherein the metal surface comprises steel and / or galvanised steel.
21. The aqueous composition B according to any one of claims 1 to 15 for use in improving the anti-corrosion pretreatment of metal surfaces comprising steel, galvanized steel, magnesium and / or zinc-magnesium alloys.
22. A concentrate from which a composition B according to claim 21 can be prepared by dilution with water and optionally setting the pH.
23. A metal surface comprising steel, galvanized steel, magnesium and / or a zinc-magnesium alloy, which is coated by a method according to any one of claims 1 to 20 and the resulting coating has a layer weight determined by XRF of: i) 5-500 mg / m 2 , based only on component a1) (calculated as zirconium), and optionally ii) 0.5-50 mg / m 2 , based solely on component a2) (calculated as silicon).
24. Use of a metal substrate coated according to the method according to any one of claims 1 to 20 in the automotive industry, rail vehicles, aerospace industry, plant construction, mechanical engineering, the building industry, the furniture industry, for the production of crash barriers, lamps, profiles, cladding or small parts, for the production of bodywork or body parts, individual components, pre-assembled or connected elements, preferably in the automotive or aerospace industry, for the production of devices or apparatuses, in particular household appliances, control devices, test devices or building elements.